Fatigue-induced glenohumeral and scapulothoracic kinematic variability: Implications for subacromial space reduction. (August 2016) - Chopp-Hurley, Jaclyn N.; O'Neill, John M.; McDonald, Alison C.; Maciukiewicz, Jacquelyn M.; Dickerson, Clark R.
Abstract: Superior humeral head translation and scapula reorientation can reduce the subacromial space. While these kinematic abnormalities exist in injured populations, the effect of muscle fatigue is unclear. Additionally, these mechanisms were typically studied independently, thereby neglecting potential covariance. This research evaluated the influence of upper extremity muscle fatigue on glenohumeral and scapulothoracic kinematics and defined their relationship. Radiography and motion tracking systems captured these kinematic relationships, during scapula plane elevation, both before and after fatigue. Fatigue-induced changes in humeral head position, scapular orientation and the minimum subacromial space width were measured. High inter-subject variability existed for each measure which precluded identification of mean differences at the population level. However, significant scapular upward rotation occurred following fatigue ( p = 0.0002). Despite similar population mean results, between 39% and 57% of participants exhibited fatigue-related changes in disadvantageous orientations. Additionally, correlations between measures were generally fair (0.21–0.40) and highly dependent on elevation, likely attributed to the variable fatigue responses. Overall, the data confirms that fatigue-induced changes in kinematics poses highly variable risk of subacromial impingement syndrome across individuals. Thus, solely considering the "average" or mean population response likely underestimates potentially injurious fatigue consequences.